Medication assisted treatment for substance use disorder - Maheen Naeem; Ammara Iqbal (Journal of the Pakistan Medical Association, 2026)
Dear Editor, We read with interest the article, ‘State of the Art Treatment Options for Pakistan’s Opioid, Alcohol, and Methamphetamine Crisis,’ which discusses medication-assisted treatment for substance use disorders (SUDs). In relation to this, new studies have highlighted the potential role of glucagon-like peptide-1 (GLP-1) in SUD.GLP-1 is an incretin hormone that regulates hunger and satiety and is produced in the small intestine and and the brainstem.1 GLP-1 Receptor Agonists (GLP-1 RA) are primarily used to treat diabetes mellitus and obesity due to their ability to slow gastric emptying and stimulate insulin production. These drugs include exendin-4, liraglutide, dulaglutide and semaglutide.However, ongoing studies are showing promising effects of GLP-1 RA use in SUD. One preclinical study by Harasta et al. demonstrated that GLP-1 RA reduces cocaine induced dopamine surges by increasing the expression of the dopamine transporter on cell surface, facilitating the removal of excess dopamine from synapses. This mechanism weakens cocaine’s rewarding effects.2 An early preclinical study on alcohol showed correspondence between GLP-1 and alcohol intake showed that male rats with a 10-week history of alcohol consumption that were treatmented with exendin-4 were found to exhibit reduced alcohol consumption.3 Now recent studies have been testing other agents such as liraglutide and semaglutide injections with similar results thus supporting the potential ofGLP-1 RA for SUD.4 In humans, one such study where diabetic patientsgiven liraglutide also reported a reduction in alcohol intake.5 Despite promisingfindings from animal studies, human data remains limited and larger clinical trials are needed to determine the effect of these drugs on humans.